2017
DOI: 10.1101/140632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of RNAseq methodologies to profile thein vivotranscriptome ofBordetella pertussisduring murine lung infection

Abstract: 16Bordetella pertussis is an obligate human respiratory pathogen that causes the disease whooping 17 cough. A whole cell vaccine (DTP) was developed in the 1940s and was subsequently replaced 18 in the 1990s with a protein-based subunit acellular vaccine (DTaP; tdap). Today, we are 19 observing a resurgence of whooping cough due to evolution of the pathogen and waning vaccine 20 immunity. The use of vaccines decreased the need for basic research on this pathogen. As a 21 result, numerous questions on the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Despite the limitations of that data set, we observed that the alcaligin siderophore biosynthesis genes were highly expressed by B. pertussis infecting the NSG mouse lung (30). Furthermore, we saw that most reads mapped to fhaB , which encodes FHA, suggesting that this gene could be highly expressed during infection.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Despite the limitations of that data set, we observed that the alcaligin siderophore biosynthesis genes were highly expressed by B. pertussis infecting the NSG mouse lung (30). Furthermore, we saw that most reads mapped to fhaB , which encodes FHA, suggesting that this gene could be highly expressed during infection.…”
Section: Resultsmentioning
confidence: 89%
“…Consequently, the NSG mouse also harbors defective macrophages and dendritic cells, with only neutrophils and monocytes unaffected by the mutations. With this in mind, we aimed to use the high bacterial burden in NSG mice to facilitate RNA-seq of infected murine lung (30). However, we were able to map only approximately 15,000 reads per 100 million to the B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations